Peranan Program Pendidikan dan Pelatihan Solo Technopark Guna Meningkatkan Kualitas SDM di Surakarta - Fina Oktafiani; Gamelli Alfius; Febbi Nur Fadillah; Atika Fina Lestari; Sri Sumaryati (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The Solo Technopark Education and Training Program aims to train participants with skills and knowledge relevant to industrial developments and current job market demands as an effort to improve the quality of Human Resources (HR) in the City of Surakarta, Indonesia. This program has advantages such as guidance from experienced mentors, practical workshops, training facilities, and competency certificates. Using a descriptive-qualitative approach, this research involved participants of the Solo Technopark Education and Training Program as research subjects. Data was obtained from interviews, observation and documentation. The research results show that graduates have high competence and can quickly adapt to the work environment. They have quality skills that suit industry needs and have the opportunity for better career development. This program collaborates with various industries to channel graduates into the world of work. Even though this program experienced fluctuations in the number of participants and the percentage of graduates absorbed in industry, the research results showed a positive impact of this program on improving the quality of human resources.